Study of Household Biodigesters - Chandra Wahyu Purnomo; Ambar Pertiwiningrum; M. Prasetya Kurniawan (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2008)
Tunnel or tubular type of bio-digester has been widely developed in many countries for producing a renewable clean fuel gas named biogas. This digester type only requires minimum maintenance and simple construction for ensuring its lower cost compared to others with similar capacity. Mostly, polyethylene (PE) plastic bag is used for construction materials of the tubular digesters. In this research, the tubular type has been constructed using large diameter PVC (Poly Vinyl Chloride) pipe for increasing the durability and safety. The performance of PVC digesters have been tested by measuring biogas production rate and CH concentration in the gas. COD (Chemical Oxygen Demand) and BOD (Biological Oxygen Demand) drop between inlet and outlet sludge have been measured for examining the digester ef- ficiency. Then, the performance was compared with PE plastic digesters data from several literatures which still needs some improvements for enhancing its capability and performance.